Nahua Cartography in Historical Context: Searching for Sources on the Mapa de Otumba. - de la Paz, María Castañeda (Ethnohistory)
The Mapa de Otumba is a colonial map from central Mexico with pictographic elements that represents a part of the señorío (lordship) of Otumba with a number of its subject towns. An analytical problem of working with this document is a lack of an accompanying text, making it difficult to understand why it was made and by whom. However, using certain archival documents, it has been possible to explore the provenance of the map. In this essay, a new date for the production of the map is proposed, with a discussion of its function as a property register of land for the community of Otumba. Beyond these important issues, it has been possible to identify the use of lands and their control and transfer from one owner to another. Ethnographic fieldwork, a vital part of the research of such a document, facilitated the identification of many of the represented places in the present-day landscape, as such showing a historical-geographic register of land from the colonial period to the present.